2021
DOI: 10.1111/1365-2745.13748
|View full text |Cite
|
Sign up to set email alerts
|

Glacier forelands reveal fundamental plant and microbial controls on short‐term ecosystem nitrogen retention

Abstract: Human activities have massively increased the amount of reactive nitrogen in the biosphere, which is leading to increased nitrogen (N) inputs in terrestrial ecosystems. The retention of N is a crucial ecosystem function of both managed and natural ecosystems, and there is a long history of experimental, observational, and conceptual studies identifying its major controls. Yet, the plant and soil microbial controls on the retention of added N remain elusive. Here, we used three ecosystem chronosequences in fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…The decrease in soil pH with increasing successional age at our study site confirms similar patterns in other earlier deglaciation chronosequences, where this soil acidification mainly results from increased soil organic matter degradation and the associated leaching of organic acids in late succession (Bernasconi et al, 2011). Compared with the studies conducted in other similar glacier forefields such as Morteratsch glacier and Damma glacier in Switzerland (Burga et al, 2010;Bernasconi et al, 2011), Rotmoosferner glacier in Austria (De Vries et al, 2021), or Hailuogou glacier in China (Jiang et al, 2018), our study aimed at considering the interplay between plants, bacteria, and fungi as well as environmental factors to detect mutual influences in the assembly of multidiverse communities. Despite the strong associations between pH and temperature with all the taxonomic groups, predictions between the composition of taxonomic groups usually showed better performance than environmental factors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The decrease in soil pH with increasing successional age at our study site confirms similar patterns in other earlier deglaciation chronosequences, where this soil acidification mainly results from increased soil organic matter degradation and the associated leaching of organic acids in late succession (Bernasconi et al, 2011). Compared with the studies conducted in other similar glacier forefields such as Morteratsch glacier and Damma glacier in Switzerland (Burga et al, 2010;Bernasconi et al, 2011), Rotmoosferner glacier in Austria (De Vries et al, 2021), or Hailuogou glacier in China (Jiang et al, 2018), our study aimed at considering the interplay between plants, bacteria, and fungi as well as environmental factors to detect mutual influences in the assembly of multidiverse communities. Despite the strong associations between pH and temperature with all the taxonomic groups, predictions between the composition of taxonomic groups usually showed better performance than environmental factors.…”
Section: Discussionsupporting
confidence: 89%
“…The time for space substitution of chronosequences allows to track soil development and the processes that shape biotic communities (Walker et al, 2010;Chang & HilleRisLambers, 2016). Multiple studies described the successional trajectories of plant, bacteria and fungi communities and the development of soil conditions along glacier forefields (Bernasconi et al, 2011;Zumsteg et al, 2012;Buma et al, 2017;Buma et al, 2019;De Vries et al, 2021). However, these studies usually focus on one or rarely two specific taxonomic groups (Ficetola et al, 2021), thus a full consideration of multidiverse communities and environmental conditions may facilitate a general evaluation of associations between different biotic and abiotic parts.…”
Section: Introductionmentioning
confidence: 99%
“…Similar correlations were found for grasslands with lower nitrogen input (De Vries et al, 2006) and for chronosequences of abandoned arable land (Van der Wal et al, 2006; Morriën et al, 2017). By contrast, De Vries et al (2021) reported that the F:B ratio did not change during ecosystem succession and concluded that increased N retention in ecosystems with a higher F:B ratio was due to low soil N availability.…”
Section: Nature-mimicry In Soil Biologymentioning
confidence: 95%
“…It thus remains unclear whether a higher F:B ratio is a driver for, or a response to, the larger amounts of soil carbon and nitrogen retained in less disturbed ecosystems or in systems with lower substrate quality (Six et al, 2006; De Vries et al, 2013; De Vries et al, 2021). Moreover, soil F:B ratios can vary for many reasons.…”
Section: Nature-mimicry In Soil Biologymentioning
confidence: 99%
“…The acceleration of glacier melting caused by global warming in recent years has created bare land in different periods which can be accurately measured, providing ideal places to study the primary succession of vegetation [ 27 , 28 , 29 ]. Most studies on vegetation succession in glacial retreat areas focus on the vegetation composition and structure, soil nutrient status and the coupling relationship of plant-soil-microbial interactions [ 30 , 31 , 32 , 33 ]. However, the N utilization strategies of dominant plants at different stages of primary succession are poorly understood, and therefore, the patterns and mechanisms for plants adjusting their N preference to adapt to environmental changes remain to be further studied.…”
Section: Introductionmentioning
confidence: 99%